TEXNOLOGIYALÍQ TÁLIM PÁNIN OQÍTÍWDÍŃ ZAMANAGÓY USÍLLARÍ HÁM RAWAJLANÍW TENDENCIYALARÍ - Kurmanov, A.P. (SCIENCE and SOCIETY, 2026)
The article examines the modern features of teaching technological education in the context of digitalization of education and the transformation of the content of school and vocational education programs. The focus is on the methodological, didactic, and organizational-pedagogical aspects of implementing the subject area of “Technological Education”, changing the structure of content, developing engineering thinking, applying digital technologies, project activities, and interdisciplinary approaches. Key problems and prospects for the development of technological education are highlighted, and the requirements for training teachers in this field are outlined.